ANALISIS SISTEM PEMBIAYAAN KPR BANK KONVENSIONAL DAN PEMBIAYAAN KPRS BANK SYARIAH (STUDI KASUS BANK BTN DENGAN BANK MUAMALAT) - FATMASARI, NABILA (Jurnal Akuntansi AKUNESA, 2013)
This paper tries to compare financing system of housing credit amongs tocommon bank and sharia bank. The purpose of this comparation is to know thedifferences of financing system of housing credit by Bank Tabungan Negara (BTN) andBank Muamalat which used to be sample. Common people only know if common bankused interest as rates in return and sharia bank did not use it. The factors will becompared are conditions apply, proccess of housing credit applied, akad or initialrequirements, calculation of installments, and treatment of customers who late inpaying or paying before the time.Keywords: akad; common bank; financing system; housing credit;interest;sharia..